Clipping electron transport and polarization relaxation of Ti3C2Tx based nanocomposites towards multifunction - Fang, Yong-Sheng; Yuan, Jie; Liu, Ting-Ting; Wang, Qiang-Qiang; Cao, Wen-Qiang; Cao, Mao-Sheng (Carbon (New York), 2023)
High-performance multifunctional electromagnetic (EM) materials exhibit great potential for development, and have attracted extensive attention from the scientific field. Generally, the dielectric "genes", including conductive networks, interfaces, and defects, are the pivotal factors that determine their performance. Herein, multifunctional Ti3C2Tx@polyaniline decorated MWCNT (TPMC) nanocomposites, containing generous dielectric "genes", were synthesized via the electrostatic self-assembly method. Thanks to the regulation of internal dielectric "genes", TPMC exhibited a tunable EM wave absorption (EMA) and EM interference (EMI) shielding performance. TPMC achieved a maximum reflection loss (RL) of −54.7 dB and an effective absorption bandwidth (EAB) of nearly 6 GHz at 1.5 mm. Moreover, the complete conductive networks endowed TPMC with a reliable EMI shielding capability. It exhibited a maximum EMI shielding effectiveness (SE) of 34 dB, and meanwhile, displayed an absorption-dominated green shielding performance. Furthermore, owing to the integration of the "genes", TPMC showed a high coulomb efficiency (∼98%) and excellent cycling stability (exceeded 95% retation after 8000 cycles), indicating a great potential as outstanding supercapacitor electrode material. This work provides a promising strategy for controlling the EM pollution and alleviating the energy issues. The Dielectric "genes" are the key core to regulate the multifunction of TPMC, which include defects, interfaces, functional groups and conductive networks. By regulating and patching the dielectric "genes" of TPMC, the multifunctional integration of EM wave absorption, EMI shielding and charge storage can be achieved. [Display omitted]